Gut microbiota of HIV-infected patients with multidrug-resistant tuberculosis - L. Yu. Otdushkina; Yu. V. Zakharova; A. A. Kholodov; L. A. Levanova; T. V. Pyanzova; A. A. Markovskaya (Фундаментальная и клиническая медицина, 2022)
Aim. To determine the composition and properties of the gut microbiota in HIV-infected patients with pulmonary tuberculosis.Materials and Methods. We studied 92 faecal samples from patients with pulmonary tuberculosis (n = 46) and patients with combined pulmonary tuberculosis and HIV infection (n = 46), with the following examination of the appearance, cultural properties, and biochemical profile of the bacteria. The constancy of microbial taxa was determined using Dazho-Odum indicator. Microorganisms were classified as constant at C > 50%, as complementary at 25% < C < 50% and as occasional at C < 25%.Results. Gut microbiota of patients with multidrug-resistant tuberculosis was consistently represented by Bifidobacterium spp., Lactobacillus spp., Enterococcus spp., Escherichia spp., Staphylococcus spp., and Candida regardless of theirHIV status. Species composition and prevalence of virulence factors in Staphylococcus spp. and fungi isolated from patients with multidrug-resistant tuberculosis also did not depend on HIV status. Complementary microorganisms were represented exclusively by Clostridium spp., while random microbiota was represented by 6 genera (Enterobacter spp., Citrobacter spp., Salmonella spp., Klebsiella spp., Proteus spp., and Pseudomonas spp.) belonging to the Proteobacteria phylum.Conclusion. Similar composition of gut microbiota in HIV-positive and HIV-negative patients with multidrug-resistant tuberculosis indicates common mechanisms of intestinal dysbiosis and a uniform approach for its correction.